Dipsocus gen. n.: A new bark louse genus of the tribe Thyrsophorini (Psocodea: Psocidae: Psocinae), with description of a new species from China - Jie, Lulan; Liang, Feiyang; Liu, Xingyue (Zootaxa, 2022)
A new bark louse genus of the tribe Thyrsophorini, namely Dipsocus gen. n., is herein described. This genus differs from the other genera of Thyrsophorini by male hypandrium divided into two parts, basal part strongly sclerotized, distal part weakly sclerotized; female pigmented area of subgenital plate roughly T-shaped, stem of T-shaped area thread-like and distally bifurcated. We also describe a new species, i.e., D. fashengi sp. n., from Guangxi, China, and provide a key to the seven Thyrsophorini genera found in China.